PENGARUH UKURAN PERUSAHAAN, KEPUTUSAN INVESTASI DAN CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP NILAI PERUSAHAAN (Studi pada Perusahaan Properti, Real Estate dan Konstruksi Bangunan yang Terdaftar di BEI Periode 2016-2017) - Aprilianto Aprilianto; Ronny Malavia Mardani; Muhammad Agus Salim (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACTThis research was conducted to determine the effect variables of firm size, investment decisions and Corporate Social Responsibility (CSR) on firm value. The type of research used in this study is explanation. The population of this research is companies in the property, real estate and building construction sectors listed on the Indonesia Stock Exchange in the period of 2016-2017 as many as 73 companies. The sampling technique was purposive sampling to obtain 54 companies that met the criteria.This research uses technical analysis of normality test, classic assumption test, multiple linear regression test and hypothesis test. The measuring instrument used to measure firm size is Ln Total Assets, for investment decisions using Price Earnings Ratio (PER), and for CSR using Corporate Social Responsibility Index company J (CSRIJ) based on the Global Reporting Initiative standard), while firm value is measured using Price to Book Value (PBV).The results of data analysis show that: (1)the firm size has a positive and insignificant effect on firm value, (2) investment decisions have a significant positive effect on firm value, while (3) CSR has a negative but not significant effect on firm value.Keywords : Firm Size, Investment Decision, Corporate Social Responsibility, Firm Value.